Magnetic Resonance Imaging and Intraoperative Frozen Sectioning for the Evaluation of Risk Factors Associated With Lymph Node Metastasis in Endometrial Cancer. Issue 8 (1st October 2013) - Hahn, Ho-Suap; Song, Heung-Seop; Lee, In-Ho; Kim, Tae-Jin; Lee, Ki-Heon; Shim, Jae-Uk; Kim, Jae-Wook; Lim, Kyung-Taek
Abstract : Introduction: To analyze the accuracy of magnetic resonance imaging (MRI) and intraoperative frozen sectioning (IFS) for predicting the low- and high-risk patients and risk factors associated with lymph node (LN) metastasis in patients with surgically staged endometrial cancer. Methods: The medical records of 175 patients with endometrial cancer who underwent comprehensive surgical staging including pelvic and para-aortic LN dissection between January 2008 and July 2011 were retrospectively analyzed. Results of MRI and IFS of the uterus for the evaluation of risk factors were correlated with final pathology. Results: Our results showed a high specificity and negative predictive value of MRI and IFS for the evaluation of myometrial invasion and cervical stromal invasion. Of the 41 patients identified as low risk by both MRI and IFS, none had pelvic or para-aortic LN metastases in the final pathology. Conclusions: The results indicate that MRI and IFS may be useful for the evaluation of risk factors associated with LN metastasis in patients with endometrial cancer. Magnetic resonance imaging and IFS can be used to accurately identify low-risk patients who do not need comprehensive surgical staging and may prevent unnecessary lymphadenectomy.